Rendemen dan Komponen Minor Minyak Sawit Mentah Berdasarkan Tingkat Kematangan Buah pada Elevasi Tinggi - Rangkuti, Ika Ucha Pradifta (Universitas Medan Area, 2018)
The Indonesian government has a vision to become the world's best sustainable palm oil producer with the aim of producing 40 million tons of palm oil in 2020 for food and for energy. The country must produce must double in the next 10 years. This condition raises black campaign from various parts of the world. Palm oil is a destroyer of the earth, but on the other hand the potential for food security in the world plays a very big role, especially for edible oil and energy.. This study aimed to determined the oil extraction rate in crude palm oil and minor components (tocol content and beta-carotene) at altitudes of 650 meters above sea level and 850 meters above sea level. This study used a completely non-factorial randomized design with parameters of unriped, riped and over riped. The results showed that the maturity level of oil palm fruit affected the oil extraction rate, beta-carotene, tocol content (tocopherol and tocotrienol) of crude palm oil produced at altitude of 650 meters above sea level and 850 meters above sea level. Riped fruit has high oil extraction rate, and the minor component were measured by tocol content and beta-carotene contained in crude palm oil.